Controlled intracellular generation of reactive oxygen species in human mesenchymal stem cells using porphyrin conjugated nanoparticles. Issue 34 (11th August 2015) - Lavado, Andrea S.; Chauhan, Veeren M.; Alhaj Zen, Amer; Giuntini, Francesca; Jones, D. Rhodri E.; Boyle, Ross W.; Beeby, Andrew; Chan, Weng C.; Aylott, Jonathan W.
Abstract : Newly synthesised Zn (ii ) porphyrin nanoparticle conjugates were irradiated with visible light to generate controlled amounts of ROS in hMSCs to advance the study of oxidative stress and cellular communication. Abstract : Nanoparticles capable of generating controlled amounts of intracellular reactive oxygen species (ROS), that advance the study of oxidative stress and cellular communication, were synthesized by functionalizing polyacrylamide nanoparticles with zinc(ii ) porphyrin photosensitisers. Controlled ROS production was demonstrated in human mesenchymal stem cells (hMSCs) through (1) production of nanoparticles functionalized with varying percentages of Zn(ii ) porphyrin and (2) modulating the number of doses of excitation light to internalized nanoparticles. hMSCs challenged with nanoparticles functionalized with increasing percentages of Zn(ii ) porphyrin and high numbers of irradiations of excitation light were found to generate greater amounts of ROS. A novel dye, which is transformed into fluorescent 7-hydroxy-4-trifluoromethyl-coumarin in the presence of hydrogen peroxide, provided an indirect indicator for cumulative ROS production. The mitochondrial membrane potential was monitored to investigate the destructive effect of increased intracellular ROS production. Flow cytometric analysis of nanoparticle treated hMSCs suggested irradiation with excitation light signalled controlled apoptotic cell death, rather than uncontrolled necrotic cell death. Increased intracellular ROS production did not induce phenotypic changes in hMSC subcultures.